Interactive Chemical Bond Electronic Module Based on Nature of Science (NoS) to Improve Scientific Literacy Knowledge - Singgih Oka Wardhana; Rusly Hidayah (Journal of Science Education Research, 2022)
PISA 2018 to improve literacy skills involves three competencies: 1) explaining phenomena scientifically, 2) evaluating and designing scientific literacy, and 3) interpreting data and evidence scientific literacy. These competencies require scientific literacy knowledge, namely content, procedural, and epistemic. The research presents the results of the interactive chemical bond e-module based on nature of science to improve scientific knowledge of scientific literacy. The method uses Multimedia Development Life Cycle (MDLC) The results of the e-module validity of each component, such as: material, scientific literacy, Nature of Science (NoS), presentation and language, are categorized as very feasible. The results of the e-module practicality of each component, such as: material, scientific literacy, Nature of Science (NoS), presentation and language, are categorized as very practical. The results of the e-module effectiveness obtained from the literacy test questions used to test the scientific knowledge of students with varying N-gain values, namely 0.81 at content knowledge, 0.84 at procedural knowledge, and 0.84 at epistemic knowledge.